Synthesis of ZnO nanostructures by microwave irradiation for energy conversion material in for dye sensitized solar cells and materials for photocatalytic dye degradation applications - Surangkana Wannapop (2019)
© 2019 The Ceramic Society of Japan. All rights reserved. ZnO nanoplates and ZnO nanostructure flowers were successfully synthesized in alkaline solutions containing different contents of sodium hydroxide by a cyclic-microwave method. The as-synthesized products were characterized by X-ray Diffraction, Field Emission Scanning Electron Microscopy and ultraviolet (UV)visible spectroscopy. The crystal structure of ZnO nanoplates and nanostructure flowers are wurtzite structure with energy band gap of 3.2013.217 eV. In this research, these products were applied as energy harvesting materials in dye sensitized solar cells (DSSCs) and also used photocatalytic degradation of methylene blue (MB) under UV irradiation. In the case of photo conversion materials, the DSSCs based ZnO nanoplates showed the best performance of photoconversion to electricity at 1.5 AM illumination. Moreover, it also well performed at dye degradation of MB under UV irradiation.